Alarming rise in vape smoking among teenagers in Pakistan: a call for action - Ameer, Muhammad Hassan; Tariq, Asma; Ali, Haider (International Journal Of Community Medicine And Public Health, 2024)
I am writing to draw attention to a matter of great concern that demands our collective awareness and action: the alarming rise in vape smoking among teenagers in Pakistan. This disturbing trend poses a serious threat to the health and well-being of our young population, and it is imperative that we address this issue promptly in a comprehensive way.